2019
DOI: 10.1002/met.1862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean mixed‐layer depth initialization on the simulation of tropical cyclones over the Bay of Bengal using the WRF‐ARW model

Abstract: The sensitivity of the simulated tropical cyclone (TC) intensity and tracks to the different ocean mixed‐layer depth (MLD) initializations is studied using coupled weather research and forecasting (WRF) and ocean mixed‐layer (OML) models. Four sets of numerical experiments are conducted for two TCs formed during the pre‐ and post‐monsoon. In the control run (CONTROL), the WRF model is initialized without coupling. In the second experiment, the WRF‐OML model is initialized by prescribing the MLD as a constant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Regional-scale coupled predictions are already operational for some TC cases in the Atlantic and North Pacific (Biswas et al, 2018;Jin et al, 2013;Saito et al, 2006), although the models used in these studies do not explicitly resolve convection. Fewer studies assess air-sea coupled models in the Bay of Bengal; the majority use mesoscale models with parameterised convection (Agrawal et al, 2020;Baisya et al, 75 2020;Greeshma et al, 2019;Yesubabu et al, 2020). They show a high sensitivity of TCs to air-sea interactions (Prakash & Pant, 2017), ocean mixed layer depth (Yesubabu et al, 2020) and ocean eddies (Anandh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regional-scale coupled predictions are already operational for some TC cases in the Atlantic and North Pacific (Biswas et al, 2018;Jin et al, 2013;Saito et al, 2006), although the models used in these studies do not explicitly resolve convection. Fewer studies assess air-sea coupled models in the Bay of Bengal; the majority use mesoscale models with parameterised convection (Agrawal et al, 2020;Baisya et al, 75 2020;Greeshma et al, 2019;Yesubabu et al, 2020). They show a high sensitivity of TCs to air-sea interactions (Prakash & Pant, 2017), ocean mixed layer depth (Yesubabu et al, 2020) and ocean eddies (Anandh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies assess air-sea coupled models in the Bay of Bengal; the majority use mesoscale models with parameterised convection (Agrawal et al, 2020;Baisya et al, 75 2020;Greeshma et al, 2019;Yesubabu et al, 2020). They show a high sensitivity of TCs to air-sea interactions (Prakash & Pant, 2017), ocean mixed layer depth (Yesubabu et al, 2020) and ocean eddies (Anandh et al, 2020). Ocean coupling in mesoscale models generally improves TC track and intensity predictions (Greeshma et al, 2019;Srinivas et al, 2016;Yesubabu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have focused on the formation of SCs over the BoB during the Pre-MS (Kotal et al 2009a;Li et al 2016Li et al , 2019a, but few studies have attempted to explain why the SC formation rate is far lower in the Post-MS than the Pre-MS. Balaguru et al (2012) indicated that the ocean barrier layer is able to prevent a sharp reduction of sea surface temperature (SST) by strengthening the stratification to weaken storminduced Ekman pumping when cyclones pass over barrierlayer regions, which is conductive to enhancement of the cyclone intensity. Unlike the Post-MS, the Pre-MS in the BoB exhibits an obvious shoaling and thin barrier layer (Thadathil et al 2007;Vissa et al 2013;Yesubabu et al 2020); therefore, the barrier layer may not explain why the Pre-MS is more prone to SC occurrence than the Post-MS. Neetu et al (2019) postulated that BoB TCs are stronger before compared with after the monsoon due to favorable large-scale background conditions; however, there is a lack of quantitative diagnostic proof to illuminate the inner physical processes that determine the difference in the SC formation rate between the Pre-and Post-MS. Considering the current situation, a more specific analysis is needed to explain what and how environmental conditions and physical processes modulate the significantly different SC formation rate between the Pre-and Post-MS in the BoB.…”
Section: Introductionmentioning
confidence: 99%